Tandem integration of circular plasmid contributes significantly to the expanded mitochondrial genomes of the green-tide forming alga Ulva meridionalis (Ulvophyceae, Chlorophyta) - Liu, Feng; Wang, Hongshu; Song, Wenli (Frontiers in Plant Science, 2022)
Comparative mitogenomics of Ulva species have revealed remarkable variations in genome size due to the integration of exogenous DNA fragments, the proliferation of group I/II introns, and the change of repeat sequences. The genus Ulva is a species-rich taxonomic group, containing a variety of green-tide forming algae. In this study, five complete mitogenomes of the green-tide forming macroalga, Ulva meridionalis R.Horimoto & S.Shimada, were assembled and compared with the available ulvophycean mtDNAs. The main circular mitogenomes of U. meridionalis ranged from 82.94 kb to 111.49 kb in size, and its 111.49-kb mitogenome was the largest Ulva mitogenome sequenced so far. The expansion of U. meridionalis mitogenomes is mainly due to the tandem integration of a 5.36-kb mitochondrial circular plasmid (pUme), as well as the proliferation of introns. An intact DNA-directed RNA polymerase gene (rpo) was present in pUme of U. meridionalis and were then detected in two putative plasmids (pUmu1 and pUmu2) found in Ulva mutabilis. The observed integration of the circular plasmid into U. meridionalis mitogenomes seems to occur via homologous recombination, and is a more recent evolutionary event. Many highly homologous sequences of these three putative plasmids can be detected in the other Ulva mtDNAs sequenced thus far, indicating the integration of different mitochondrial plasmid DNA into the mitogenomes is a common phenomenon in the evolution of Ulva mitogenomes. The random incidence of destruction of plasmid-derived rpos and open reading frames (orfs) suggests that their existence is not the original characteristic of Ulva mitogenomes and there is no selective pressure to maintain their integrity. The frequent integration and rapid divergence of plasmid-derived sequences is one of the most important evolutionary forces to shape the diversity of Ulva mitogenomes.